2014
DOI: 10.1007/s00018-014-1773-2
|View full text |Cite
|
Sign up to set email alerts
|

Aquaglyceroporins: implications in adipose biology and obesity

Abstract: Aquaporins (AQPs) are membrane water/glycerol channels that are involved in many physiological processes. Their primary function is to facilitate the bidirectional transfer of water and small solutes across biological membranes in response to osmotic gradients. Aquaglyceroporins, a subset of the AQP family, are the only mammalian proteins with the ability to permeate glycerol. For a long time, AQP7 has been the only aquaglyceroporin associated with the adipose tissue, which is the major source of circulating g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 112 publications
0
73
0
Order By: Relevance
“…There are up to 13 mammalian AQPs, which are found in most tissues with functions ranging from the regulation of renal water balance [1], brain-fluid homeostasis [2], triglyceride cycling between adipocytes and the liver [3] and structural integrity of the eye lens [4]. Because of this, understanding AQP function is crucial for the study of healthy ageing as well as the onset of many disease states such as brain swelling following stroke or head injury [5], nephrogenic diabetes insipidus [6,7], cataracts [8], obesity [9], cancer cell proliferation and migration [10] and tumour angiogenesis [11]. Many of these functions and diseases involve either permeability of molecules other than water, or a function of the AQP other than facilitating membrane permeability.…”
Section: Introductionmentioning
confidence: 99%
“…There are up to 13 mammalian AQPs, which are found in most tissues with functions ranging from the regulation of renal water balance [1], brain-fluid homeostasis [2], triglyceride cycling between adipocytes and the liver [3] and structural integrity of the eye lens [4]. Because of this, understanding AQP function is crucial for the study of healthy ageing as well as the onset of many disease states such as brain swelling following stroke or head injury [5], nephrogenic diabetes insipidus [6,7], cataracts [8], obesity [9], cancer cell proliferation and migration [10] and tumour angiogenesis [11]. Many of these functions and diseases involve either permeability of molecules other than water, or a function of the AQP other than facilitating membrane permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Association of AQP9 with BP regulation is unclear; however, 1 study found that it was upregulated in preeclamptic placenta . AQP9, in coordination with AQP7, may regulate adiposity and glucose homeostasis . Notably, other members of the aquaporin family (AQP1, AQP2, and AQP4) have been associated with BP in animal studies …”
Section: Discussionmentioning
confidence: 99%
“…The radioactive label in arachidonoyl [1][2][3] H]ethanolamine is in the ethanolamine moiety, which is quickly cleaved and then incorporated into phospholipids [ 7 -9 ]. Therefore, the radioactive signal associated to the organic phase of the cell pellets is derived from free [ H]glycerol freely and rapidly moves out of the cell via aquaporins, leading to a "loss" of intracellular radioactive signal [ 10 ]. The remaining signal is therefore only dependent on intracellular arachidonoyl [1,2, H]glycerol [ 7 ].…”
Section: Notesmentioning
confidence: 99%